YAG capsulotomy rates between two types of trifocal intraocular lenses - Muhammad Ali; Ali Bin Abdul Jabbar; Muhammad Haris Zahid; Irfan Jeeva; Muhammad Abdul Rehman Siddiqui (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate YAG capsulotomy rates following implantation of two types of trifocal intraocular lenses (IOLs). Methods: In this retrospective cohort study consecutive patients who underwent cataract surgery with a trifocal IOL from 1st May 2017 to 30th October 2019 at Aga Khan University Hospital, Karachi were included. Eyes which either had an AT Lisa Tri or Alcon PanOptix IOL implant were included. The primary outcome measure was Nd: YAG laser. Univariate analysis of all predictor variables was performed followed by a multivariate regression analysis of those which were significant. A p-value of < 0.05 was taken as significant. Results: A total of 328 eligible eyes were identified. Nine eyes were excluded. Out of the 319 eyes of 177 patients included in this study, 180 received AT Lisa Tri while 139 of them received Alcon PanOptix Trifocal IOLs. The mean (SD) age of the patients was 52.29 years (±11.04). Gender was equally distributed with 91 male patients (51.4%). Median (IQR) time to laser capsulotomy was 8 months (3-16). Clinically posterior capsular opacification (PCO) was present in 75 eyes (23.5%). A total of 39 eyes (12.2%) underwent Nd: YAG laser capsulotomy. Among the AT Lisa Tri group 29 eyes (16.1%) underwent laser capsulotomy compared to 10 (7.2%) (n=10) in Alcon PanOptix group (p=0.016). In both univariate and multivariate analyses, gender and IOL type were statistically significant. ---Continue